"But what if they call the police?" - Loughran, Maureen (Muzikološki zbornik, 2008)
This article explores the difficulties and necessities of applied ethnomusicological research in an urban American neighborhood. A theory of method for activist centered work which connects academia with local, grassroots communities is discussed as well as the challenges of positioning oneself as an applied ethnomusicologist in the field.
Keywords: aplikativna etnomuzikologija; glasba; lokalne skupnosti; music; urbana kultura